Un nuevo Discomycete operculado de America Central: Morchella herediana, nov. sp. - Gomez, L. D.
vol: 16 / no: 3-4 / p.417-426 / Inv: 06-R00179-ej.1 01-R08785-ej.2 02-R05947-ej.3 / ST: AR-D/1 v 16 no 3/4
En: vol 16, no 3-4
Keywords: Hongos; Discomycetes; Morchella